Pengaruh Kepuasan Agen, Kualitas Layanan, dan Kualitas Produk terhadap Loyalitas Agen Penyalur Cat Mowilex di Wilayah Yogyakarta - Ahmad Rodli Setyoko; Andriya Risdwiyanto (Jurnal Manajemen Strategis: Jurnal Mantra, 2024)
Businesses with increasingly competitive competition require companies to understand the factors that influence agent loyalty. This research uses quantitative methods and random sampling to determine the sample. Respondents were selected from a list of Mowilex paint distribution agents in Yogyakarta, totaling 124 people with a sample of 95 respondents. The results of this research indicate that the independent variable accounts for 66.5% of the variation in the dependent variable. Meanwhile, agent satisfaction and product quality do not have a significant effect on agent loyalty. On the other hand, service quality has a considerable impact on agent loyalty. Overall, agent satisfaction, product quality, and service quality have a significant effect on agent loyalty simultaneously.